A photoinduced mixed valence photoswitch - Cotic, Agustina Ludmila (2022)
The ground state and photoinduced mixed valence states (GSMV and PIMV, respectively) of a dinuclear (Dp4+) ruthenium(ii) complex bearing 2,2′-bipyridine ancillary ligands and a 2,2′:4′,4′′:2′′,2′′′-quaterpyridine (Lp) bridging ligand were investigated using femtosecond and nanosecond transient absorption spectroscopy, electrochemistry and density functional theory. It was shown that the electronic coupling between the transiently light-generated Ru(ii) and Ru(iii) centers is HDA ∼ 450 cm−1 in the PIMV state, whereas the electrochemically generated GSMV state showed HDA ∼ 0 cm−1, despite virtually identical Ru-Ru distances. This stemmed from the changes in dihedral angles between the two bpy moieties of Lp, estimated at 30° and 4° for the GSMV and PIMV states, respectively, consistent with a through-bond rather than a through-space mechanism. Electronic coupling can be turned on by using visible light excitation, making Dp4+ a competitive candidate for photoswitching applications. A novel strategy to design photoinduced charge transfer molecular switches is proposed.